CGIAR Initiative on Market Intelligence - Demont, Matty; Bayot, Ruvicyn; Connor, Melanie; Dixit, Shalabh; Veettil, Prakashan; Lenaerts, Bert; Paguirigan, Neale Marvin; Pede, Valerien (2023)
“CGIAR and its partners maximize investment returns in breeding, seed systems and other Initiatives a cross the 5 Impact Areas based on reliable and timely market intelligence. Stronger demand orientation generated by market intelligence strengthens co-ownership and co-implementation by CGIAR, NARES, private sector, and NGOs, leading to more strategic efforts to getting high quality products into the fields of women and men smallholder farmers, enhancing livelihoods and diets of populations at large.”